Case report: Improvement in refractory functional seizures, depression, and quality of life with ketamine-assisted therapy - Argento, Elena; Omene, Egiroh; Jaeger, Alexandria H.; Kertes, Angela; Mitchell, Kaitlyn A.; Necyk, Candace; Thielking, Paul; Lewis, Evan Cole (Frontiers in Neuroscience, 2023)
Functional seizures, a primary subtype of functional neurological disorder (FND), are a known cause of serious neurological disability with an increasing awareness of their impact amongst the neuroscience community. Situated at the intersection of neurology and psychiatry, FND is characterized by a range of alterations in motor, sensory or cognitive performance, such as abnormal movements, limb weakness, and dissociative, seizure-like episodes. Functional seizures are known, in part, to have psychological underpinnings; however, the lack of effective and consistent treatment options requires research and novel approaches to better understand the etiology, diagnosis and what constitutes a successful intervention. Ketamine, a selective blocker of the N-methyl-D-aspartate receptor, has a well-established safety and efficacy profile. In recent years, ketamine-assisted therapy has shown increasing potential for treating a broad range of psychiatric conditions, building on its demonstrated rapid-acting antidepressant effects. Here we present a 51-year-old female with refractory daily functional seizures leading to significant disability and a medical history significant for major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). After unsuccessful treatment attempts, the patient underwent a novel protocol with ketamine-assisted therapy. After 3 weeks of ketamine-assisted therapy followed by 20 weeks of intermittent ketamine treatment and ongoing integrative psychotherapy, the patient’s seizures were significantly reduced in frequency and severity. She experienced significant improvements in depressive symptoms and functional ability scores. To our knowledge, this is the first reported case describing improvement in functional seizures following ketamine-assisted therapy. While rigorous studies are needed, this case report encourages further investigation of ketamine-assisted therapy for functional seizures and other functional neurological symptoms.